Integration of Urine-Charged Biochar and Chemical Fertilizers Enhances Cauliflower Productivity in Inceptisols - Jaishi, Ajay; Khanal, Babu Ram; Bhatta, Sandesh (Journal of Agriculture and Forestry University, 2025)
Cauliflower (Brassica oleracea var. botrytis) cultivation in Nepal relies heavily on chemical fertilizers, degrading soil microbes and causing nutrient imbalances. Judicious organic-inorganic fertilizer use is vital for sustainable yields. A field experiment was conducted in Rampur, Chitwan, Nepal, (November-February 2019) to evaluate the effects of urine-charged biochar (UCB) and recommended dose of chemical fertilizers (RDF) on growth and productivity of cauliflower in Inceptisols. The experiment followed a Randomized Complete Block Design (RCBD) with six fertilizer treatments: control (no fertilizer), UCB 100%, RDF 100%, and their combinations (UCB 75% + RDF 25%, UCB 50% + RDF 50%, UCB 25% + RDF 75%), replicated four times. Lantana camara biochar, produced via low-cost Kon-Tiki slow pyrolysis, was mixed with cattle urine (1:1 w/w) and applied to the root zone. Plant height, leaf number, canopy diameter, stem weight, root length, root weight, and yield differed significantly (p<0.05) among treatments. The UCB 50% + RDF 50% treatment produced the highest yield (47.3 Mt ha-1) and biological yield (92.35 Mtha-1), surpassing RDF 100% by 24.9% (yield) and 14.9% (biological yield), and UCB 100% by 9.8% (yield) and 7.0% (biological yield). The experiment demonstrates that combined UCB and chemical fertilizer application enhances cauliflower yield and yield attributes compared to sole applications.